Sie sind auf Seite 1von 2

142 CHAPTER 3 Linear and Quadratic Functions

3 . 3 A s se s s Your Unde r s t a n d ]

'Are You Prepared?'

are given at the end of these exercises. If you get a wrong answer, read the pages listed in red.

1. List the intercepts

2. Find the real solutions (pp, A4~-;\) 1)

of the equation

y = x2 - 9. (pp, 11-12)

2x2 + 7x - 4 = 0.

of the equation

3. To complete

the square

. (pp. A47-A4~)

of

X2 - 5x, you add the number

4. To graph y = (x - 4)2, you shift the graph of y = x2 to the

a distance

of

units. (pp.Y2-IOO)

Concepts and Vocabulary

 5. graph of a quadratic The function is called a(n) . 6. vertical line passing through the vertex of a parabola The

called the

is

7. The x-coordinate

.

True or False

8.

of the vertex

of f(x)

= ax' + b x + c,

a v: O,is

The graph of f (x) = 2x2 + 3x - 4 opens up.

9. True or False

The y-coordinate

10.

-x 2

True or False

+ 4x + 5 is f(2).

If the

discriminant

of the vertex

of f(x)

=

b 2 - 4ac = 0, the graph of

f(x)

= ax: + b x + c, a -:/-0, will touch

the x-axis

at its

vertex.

Skill Building

In Problems 11-18, match each graph to one the following functions.

 11. f ( x) = x2 - 1 12. f ( x) = - X2 - 1 15. f(x) = x2 - 2x + 2 16. f(x) = x2 + 2x A y Bye 32 2 2 x -2 ! 2 x (-1,0) -1 (-1, -1) I -2 E y F y 1 -2 -1 (1,0) 3 x -2

13.

17. f(x)

f ( x) = x2 - 2x + 1

= x2 - 2x

 y -2 2 x (0, -1) -2 G y -1 3 x -1

14. f(x)

= x2 + 2x + 1

 18. f ( x) = x2 + 2x + 2 D y 3 (-1,1) -2 2 x -1 H y 2 -2 x (1, -1) -2

In Problems 19-34, graph the function f by starting with the graph of y = x2 and using transformations and/or reflection).

(shifting, compressing, stretching,

 [Hint: H necessary, write fin the formf(x) = a(x - h)2 + k.] 1 19. f(x) = "4X2 20. f(x) = 2x2 21. 1 23. f(x) = "4x2 + 2 24. f(x) = 2x2 + 4 25. 2 7 . f(x) = x2 + 4x + 2 28. f(x) = x2 - 6x - 1 29. 31. f(x) = -x 2 - 2x 32. f(x) = _2x2 + 6x + 2 33.

1

f (x) = "4 X2 - 2

f(x)

1

= "4x2 + 1

f(x)

= 2x2 - 4x + 1

f

1

( x) = 2 x2 + x-I

 22 f(x) = 2X2 - 3 26 f(x) = -2x 2 - 2 30 f(x) = 3x 2 + 6x

34 f(x)=-x

·33

2

2

+-x-l 4

its vertex, axis

of symmetry, y-intercept, and x-intercepts, if any. (b) Determine the domain and the range of the function. (c) Determine where the function is increasing and where it is decreasing.

In Problems 35-52, (a) graph each quadratic function by determining

whether its graph opens up or

down and by finding

 J5 . f(x) = X2 + 2x 36. f(x) = x2 - 4x 37. f(x) = -x 2 - 6x 38. f(x) = -x 2 + 4x 39. f(x) = 2x2 - 8x 40. f(x) = 3x 2 + 18x 41. f(x) = x2 + 2x - 8 42. f(x) = x2 - 2x - 3 43 . f(x) = X2 + 2x + 1 44. f (x) = X2 + 6x + 9 45. f (x) = 2X2 - X + 2 46. f(x) = 4x2 - 2x + 1

.,

.,

SECTION 3.3 Quadratic Functions and Their Properties

143

47. f(x)

50. f(x)

=

-2x 2

+ 2x -

3

= 2x2 + 5x + 3

 48 f(x) = -3x 2 + 3x - 2 51 f(x) = _4x2 - 6x + 2

In Problems 53-58,

53.

y

54.

whose graph is given .

y

56.

-1

5 x

In Problems 59-66, determine, without then find the value.

57.

-1

234

5 x

x

-4 Vertex: (1, -3)

graphing, whether the given quadratic function

 49. f(x) = 3x 2 + 6x + 2 52. f(x) = 3x 2 - 8x + 2 55. Vertex: (-3, 5) 1 x 58. y Vertex: (-2, 6) 6 has a maximum value or a minimum value and
 59 f(x) = 2x2 + 12x 62 f(x) = 4x2 - 8x + 3 65 f(x) = -3x2 + 12x + 1
 60 f(x) = _2x2 + 12x ., 61. f(x) = 2X2 + 12x - 3 63 f(x) = -x 2 + lOx - 4 64. f(x) = _2x2 + 8x + 3 66 f(x) = 4X2 - 4x

Applications and Extensions

67. The graph of the function

f(x)

tex at (0,2) and passes through

and c.

= ax' + bx + c has ver- the point (1,8). Find a, b,

In Problems

69-74, for the given functions

f and g,

68. The graph of the function

f(x)

tex at (1,4) and passes through the point (-1, -8). Find a, b, and c.

= ax: + bx + c has ver-

 (a) Graph f and g on the same Cartesian plane. (b) Solve f(x) = g(x). (c) Use the result of part (b) to label the points of intersection of the graphs off and g. (d) Shade the region for which f( x) > g( x), that is, the region below f and above g.
 69 f(x) = 2x - 1; g(x) = X2 - 4 70. f(x) = -2x - 1; g(x) = x2 - 9 71 f(x) = -x 2 + 4; g(x) = -2x + 1 72. f(x) = -x 2 + 9; g(x) = 2x + 1 73 f(x) = -x 2 + 5x; g(x) = x2 + 3x - 4 74. f(x) = -x 2 + 7x - 6; g(x) = x2 + X - 6